Culture and politics in economic development - Bornschier, Volker, 1944- (London ; New York : Routledge, 2005)
In this important book, Volker Bornschier analyzes growth and development in the Old and New Worlds - the so-called 'developed' countries. He shows how sociological and political factors have a massive impact on economic change in those countries. The book should prove to be a significant contribution to the burgeoning literature on social capital, trust and democracy
Includes bibliographical references (p. [273]-290) and index.
oif 31/01/14
Loan
Keywords: Economic development -- Sociological aspects; Economic development -- Social aspects; Economics -- Sociological aspects